Strategi Pengembangan Kurikulum Merdeka Belajar Kampus Merdeka Berbasis Individual Differences Pada Perguruan Tinggi - Nur Arifin; Jihan Jihan; Mohammad Edy Nurtamam; Astuti Cendrawati Ramli; Windy Wonmaly; Jemi Pabisangan Tahirs (Departement of Mathematics Education, 2023)
The Merdeka Learning Independent Campus curriculum aims to improve the competence of graduates by equipping students with various types of skills, both soft skills and hard skills needed by the world of work. The development of the Merdeka Learning-Campus Merdeka curriculum in the Trunojoyo Madura University Early Childhood Education Teacher Education Study Program based on individual differences in Higher Education is expected that students can understand the character and diversity of students as a basis for being able to play a role as educators and education personnel, consultants in the field of PAUD and teacherpreneurs. The method used is descriptive research method with quantitative approach. The research subjects were 93 students from the 2021-2023 batch, and 12 lecturers who taught in the PG-PAUD Study Program. The stages of research implementation include: Focus group discussions, workshops, instrument making, field surveys, data processing and analysis, results seminars and socialization. This research was conducted for 3 weeks at Trunojoyo University Madura. Data collection techniques using a questionnaire that contains aspects of curriculum implementation strategies, namely: planning, curricular documents, human resources, administration, infrastructure, and cultural climate. The results of the validation test conducted on 30 items, obtained 26 valid items, and 4 invalid items, so the research team decided to use 26 valid items for the data collection process. The reliability result shows 0.869 which can be categorized that the questionnaire distributed is reliable to describe the curriculum development strategy for independent campus learning based on individual differences in higher education.